Crystal structure of 2-(1,3-dioxoindan-2-yl)isoquinoline-1,3,4-trione - Ghalib, Raza Murad; C. S., Chidan Kumar; Hashim, Rokiah; Sulaiman, Othman; Fun, Hoong Kun (International Union of Crystallography, 2015)
In the title isoquinoline-1,3,4-trione derivative, C18H9NO5, the five-membered ring of the indane fragment adopts an envelope conformation with the nitrogen-substituted C atom being the flap. The planes of the indane benzene ring and the isoquinoline-1,3,4-trione ring make a dihedral angle of 82.06 (6). In the crystal, molecules are linked into chains extending along the bc plane via C—H O hydrogen-bonding interactions, enclosing R2 2(8) and R2 2(10) loops. The chains are further connected by – stacking interations, with centroidto- centroid distances of 3.9050 (7) A ° , forming layers parallel to the b axis.